2007
DOI: 10.1002/ange.200604774
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerenangereicherte Cyclopropene: vielseitige Bausteine in der asymmetrischen Synthese

Abstract: Enantiomerenangereicherte Cyclopropenderivate, die kleinstmöglichen ungesättigten Carbocyclen, sind von großem Interesse für die Synthese, da sie als vielseitige reaktive Bausteine eingesetzt werden können. Die Reaktivität rührt von der Ringspannung her, die durch Umsetzungen gemildert wird. Die Cyclopropenderivate können zu komplexeren chiralen Strukturen umgesetzt werden, wobei in diesem Aufsatz besonders die Herstellung von enantiomerenangereicherten Methylen‐ und Alkylidencyclopropanderivaten herausgehoben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 108 publications
0
22
0
6
Order By: Relevance
“…A novel [2,3]-rearrangement of cyclopropenylmethyl phosphinites to methylenecyclopropylphosphane oxides was demonstrated by Rubin et al [85] As shown in Scheme 38, these authors developed the one-pot transformation of alcohols 112a-d into diasteromeric mixtures of methylenecyclopropylphosphane oxides 114a-e and 115a-e without the isolation of the sensitive phosphinites 113a-d in high yields and moderate diastereoselectivities of up to 68% de. It was found that, in striking contrast to the analogous rearrangement known for unstrained allylic systems, this reaction did not proceed at all upon thermal activation; however, it could be efficiently mediated by a base such as DBU.…”
Section: Nucleophilic Displacementsmentioning
confidence: 96%
See 4 more Smart Citations
“…A novel [2,3]-rearrangement of cyclopropenylmethyl phosphinites to methylenecyclopropylphosphane oxides was demonstrated by Rubin et al [85] As shown in Scheme 38, these authors developed the one-pot transformation of alcohols 112a-d into diasteromeric mixtures of methylenecyclopropylphosphane oxides 114a-e and 115a-e without the isolation of the sensitive phosphinites 113a-d in high yields and moderate diastereoselectivities of up to 68% de. It was found that, in striking contrast to the analogous rearrangement known for unstrained allylic systems, this reaction did not proceed at all upon thermal activation; however, it could be efficiently mediated by a base such as DBU.…”
Section: Nucleophilic Displacementsmentioning
confidence: 96%
“…The [2,3]-sigmatropic rearrangement of allylic diphenylphosphinites 117a-g generated from the corresponding alcohols 116a-g was also investigated by Marek et al [82] As shown in Scheme 39, primary, secondary and tertiary cyclopropenyldiphenylphosphinite derivatives 117a-d were rearranged within a few minutes into the corresponding phosphane oxide of methylene-and alkylidenecyclopropanes 118a-d in excellent yields. As the design and preparation of chiral phosphanes for asymmetric catalysis is an active area of research, the scope of the methodology was extended to chiral cyclopropenyldiphenylphosphinites 117e-g which provided the corresponding (E)-and (Z)-alkylidenecyclopropane diphenylphosphane oxide derivatives 118e, f in an 80:20 E/Z ratio with a complete transfer of chirality, as shown in Scheme 39.…”
Section: Nucleophilic Displacementsmentioning
confidence: 97%
See 3 more Smart Citations